Microstructural and mechanical properties of geopolymers based on brick scrap and fly ash - Felix Kugler; Thomas Fehn; Maximilian Sandner; Wolfgang Krcmar; Ulrich Teipel (International Journal of Ceramic Engineering & Science, 2022)
Abstract In the present work, the influence of increasing brick scrap additions on the setting behavior and material properties of fly ash‐based geopolymers is investigated. The geopolymers produced are tested for their compressive strengths, bulk densities, and thermal conductivities, among other properties. Both the starting materials and the produced geopolymers are also investigated by infrared spectroscopy, X‐ray diffraction analysis, and scanning electron microscopy to show the relationship between the solidification behavior and the resulting material properties. The investigations show that brick scrap is very suitable as a matrix material for geopolymer production. Increasing brick scrap additions lead, among other things, to a reduction in bulk density, thermal conductivity and compressive strength.